Time components contributing to door-to-balloon time of patients with ST-elevation myocardial infarction - Setiawan, Dion; Anjarwani, Setyasih; Rohman, Mohammad Saifur (Universitas Brawijaya, 2025)
Timely percutaneous coronary intervention (PCI) for patients experiencing ST-segment elevation myocardial infarction (STEMI) can greatly decrease mortality and morbidity. However, delays can hinder its effectiveness. The interval from hospital admission to reperfusion with PCI, known as door-to-balloon time (D2B), is closely linked to patient outcomes and is a key indicator of hospital quality. European guidelines suggest a D2B time of 90 minutes or less. Furthermore, some registries break down the D2B time into component times. These components include the time needed to identify a STEMI and activate the catheterization lab (door-to-activation time), the time for lab preparation and patient transport (activation-to-laboratory time), and the time from lab arrival to the initial use of devices to open the blocked artery (laboratory-to-balloon time). In Indonesia, factors such as population diversity, cultural beliefs, health literacy, and national insurance processes may affect D2B times. Understanding these components can help develop strategies to reduce delays. Understanding each component of D2B time and its contributing factors can aid physicians in developing effective strategies to reduce D2B delays.